DETERMINATION OF BIOLOGICAL ACTIVITIES OF THREE MARINE ALGAE COLLECTED FROM VISAKHAPATNAM COAST - S, SATYALAKSHMI (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Determination of biological activities of marine algae collected from the Visakhapatnam coastal region. Methods: Antibacterial activity of algal extracts determined by the well diffusion method, antioxidant activity was determined by reducing power (RP) method and 1, 1-diphenyl-2-picryl-hydrazil (DPPH) radical scavenging method finally anti-inflammatory activity was determined by human red blood cell stabilization method and egg albumin method. Results: Methanolic extracts of three algae have potential inhibition activity against Escherichia coli, Bacillus subtilis, Pseudomonas aeruginosa, and Staphylococcus aureus. Green alga Enteromorpha compressa has better antioxidant activity compared to the Gracilaria arcuata and Ulva fasciata when tested in RP and DPPH method. U. fasciata found good anti-inflammatory activity among the selected three algae. Conclusion: The three tested algae exhibited significant antibacterial and antioxidant activity compared to anti-inflammatory activity. These bioactive compounds containing macroalgae may find their commercial potential in medicine, food, and cosmetic industry